DESIGN AND CONSTRUCTION OF FISH WASHING MACHINE - Ogundana, Odunayo Seyi; Iluyemi, Ayodele Clark; Akande, Olalekan Ahmed (FUDMA JOURNAL OF SCIENCES, 2025)
This study aimed to design and construct a fish washing machine, detailing its operational principles and maintenance requirements. The primary objective was to develop, build, and evaluate a prototype that integrates mechanical safety features. The project centers on an electrically powered fish washing machine, which operates by converting electrical energy into rotary motion to facilitate the washing process. Fish washing is a critical component of fish processing; however, many processors find it to be an undesirable and labor-intensive task. The advent of fish washing machines has significantly reduced the time required for this process, thereby minimizing the need for manual labor. Despite the advantages, the existing machines on the market are predominantly imported and costly, creating a barrier for fish processors in our country, where over 50% of the population lives in extreme poverty. These processors often lack the financial means to purchase imported machines and the expertise required for their operation. The machine developed in this project has a capacity of 50 kg/hr, compared to the 20 kg/hr achievable through manual washing. It can wash 10 kg of fish under 10 minutes, with a shaft diameter of 0.0795 mm and an outer cylinder failure stress of 0.985 mm. This project emphasizes the local design and fabrication of an electric motor-powered fish washing machine.
Keywords: Design; Washing Machine; Fish; Shaft; Bearing